Mechanical Behavior and Damage Fracture Mechanism of Deep Rocks - Yang, Sheng-Qi. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents mainly experimental studies on the mechanical behavior and damage fracture mechanism of deep rocks including sandstone, marble, mudstone and granite, combining with several advanced technologies of X-ray micro-CT and AE monitoring. It has several unique features: 1) Investigates the influence of loading path on triaxial strength and deformation behavior of sandstone and marble; 2) Analyzes the effect of borehole size on triaxial strength and deformation behavior of hollow sandstone; 3) Explores the influence of high temperature on triaxial deformation and permeability behavior of sandstone and granite; 4) to reveal the damage fracture mechanism of deep rocks using spatial AE techniques and X-ray micro CT observations. This work will appeal to a wide readership from technicians in the field of geotechnical engineering and engineering geology to scholars carrying out research in the rock mechanics.
Chapter 1. Introduction -- Chapter 2. Strength and failure behavior of layered sandstone under uniaxial compression and Brazilian test -- Chapter 3. Strength, deformation and damage evolution behavior of red sandstone under triaxial compression -- Chapter 4. Mechanical damage characteristics of red sandstone under triaxial cyclic loading -- Chapter 5. Strength and deformation behavior of red sandstone under simple and complex loading paths -- Chapter 6. Mechanical and fracture behaviors of yellow sandstone under triaxial monotonic and cyclic loading -- Chapter 7. Triaxial strength and deformation failure behavior of coarse marble under six different loading paths -- Chapter 8. Deformation failure characteristics of crystalline marble under triaxial cyclic loading -- Chapter 9. Strength, deformation and fracture behavior of deeply-buried marble under different confining pressures -- Chapter 10. Mechanical behaviour and damage fracture mechanism of shale under Brazilian compression -- Chapter 11. Mechanical behavior and brittleness characteristics of Longmaxi formation shale under triaxial compression -- Chapter 12. Deformation and damage failure behaviour of mudstone under single-stage and multi-stage triaxial compression -- Chapter 13. Deformation, peak strength and crack damage behavior of hollow sandstone under conventional triaxial compression -- Chapter 14. Fracturing mechanism of compressed hollow-cylinder sandstone evaluated by X-ray micro-CT scanning -- Chapter 15. Fracture evolution mechanism of hollow sandstone by X-ray micro-CT observations and 3-D numerical simulations -- Chapter 16. Thermal damage and uniaxial mechanical behavior of granite after exposure to different high temperature treatments -- Chapter 17. Triaxial mechanical and permeability behavior of sandstone after exposure to different high temperature treatments -- Chapter 18. Effect of high temperature on the permeability evolution and failure response of granite under triaxial compression.
Keywords: Geotechnical engineering; Mechanical engineering; Geotechnical Engineering and Applied Earth Sciences; Mechanical Engineering